From vivid to dull: color in “Indians of Brazil” by Vitor Nogueira - Ramos, Aline Cristina Gomes; Araújo, Giulia dos Santos (Revista do Colóquio, 2023)
This text is an experience report of the work carried out, since 2022, at the Conservation and Restoration Center of the Federal University of Espírito Santo. For now, the objective is to present preliminary results of the research and analyzes carried out when intervening in large-format color photographs, discussing here the case study of the remains of the series “Indians of Brazil”, partially exhibited at the aforementioned University in 1995. Authored by photographer/artist Vitor Nogueira, the reflection on what was produced and its current state of conservation allows for a technical and poetic assessment in relation to the use of color.